Testicular Involvement in Sarcoidosis: A Rare Presentation - Campos Pinto, Catarina; Cristiana Fernandes Machado, Filipa; Sofia Ribeiro Martins, Paula (Gazeta Médica, 2025)
Sarcoidosis is a multisystem granulomatous disease with a challenging diagnosis due to the multiplicity of possible clinical presentations. A 34-year-old man presented with recurrent episodes of right testicular pain and dysuria after sexual intercourse, without hematospermia, pain during penetration, or urethral discharge. He had no risky sexual behaviors. Testicular ultrasound revealed bilateral vascularized testicular lesions, the largest being 6 mm. Subsequent studies showed elevated transaminases, lactate dehydrogenase, and angiotensin-converting enzyme. Imaging with a thoraco-abdomino-pelvic computed tomography scan revealed multiple micronodularities in the testicles, lungs, liver, spleen, and lymph nodes. A liver biopsy revealed non-caseating granulomatous hepatitis lesions, supporting the diagnosis of sarcoidosis with testicular involvement. Therefore, the diagnosis of genitourinary sarcoidosis is demanding and should be considered in the presence of nonspecific genitourinary manifestations, testicular nodularity, and/or infertility. It is crucial to correctly differentiate it from neoplastic disease to avoid unnecessary treatments with irreversible sequelae.